الفلاح الأندلسي من القرن 2-6 هـ /8 -12م - زروانة، غزالة, الغول، نبيلة (جامعة الوادي university of Eloued, 2019)
الملخص: تناولت هده الدراسة الفلاح الأندلسي نظرة جديدة حول طبيعة حياة المجتمع الأندلسي والدي مثل بدوره مساهمة كبيرة في التراث العربي الإسلامي فيما يتعلق بالزراعة كأحد جوانب الاقتصاد،فقد برع الفلاح الأندلسي في معالجة التربة وتصنيف الأراضي كما تميز بالعديد من الخبرات كخبرات السقي وحفظ المنتوج ،كما ابتكر الفلاح مجموعة من الأدوات وقد تمكن الفلاح الأندلسي من مواجهة بعض المشاكل كمشكلة الضرائب والسلطة وبعض المشاكل الطبيعية . Résumé : This Andalusian peasant study examined the nature of Andalusian society and its role in the Arab-Islamic heritage in terms of agriculture as one aspect of the economy. The Andalusian farmer excelled in soil treatment and land classification. He also distinguished himself with many experiences such as watering and preserving the product. A set of tools has enabled the Andalusian peasant to face some problems such as the problem of taxes and power and some natural problems.
مذكرة ماستر تاريخ تخصص تاريخ الغرب الإسلامي في العصر الوسيط
Keywords: الفلاحة الأندلسية، الزراعة في الأندلس; Agriculture andalouse, agriculture en Andalousie; Andalusian agriculture, agriculture in Andalusia